A two stage data envelopment analysis model with undesirable output - Adam Shariff Adli, Aminuddin; Nor Izzati, Jaini; Maznah, Mat Kasim; Mohd Kamal, Mohd Nawawi (IOP Publishing Ltd, 2017)
The dependent relationship among the decision making units (DMU) is usually assumed to be non-existent in the development of Data Envelopment Analysis (DEA) model. The dependency can be represented by the multi-stage DEA model, where the outputs from the precedent stage will be the inputs for the latter stage. The multi-stage DEA model evaluate both the efficiency score for each stages and the overall efficiency of the whole process. The existing multi stage DEA models do not focus on the integration with the undesirable output, in which the higher input will generate lower output unlike the normal desirable output. This research attempts to address the inclusion of such undesirable output and investigate the theoretical implication and potential application towards the development of multi-stage DEA model.